Savoring dan kecerdasan adversity pada siswa - Fajrin, Nisa Mu’alimah; Isti'adah, Feida Noor Laila; Sugara, Gian Sugiana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
The purpose of this study was to find a general description of savoring and adversity intelligence in students and to find a correlation between them. Savoring students explain strategies to increase positive experiences in their lives and overcome negative experiences to become positive by appreciating their experiences. This is illustrated by evaluating aspects of anticipating the future, enjoying present experiences, reminiscing about positive experiences in the past. Literature review revealed that the factor of being unable to be grateful and adversity intelligence has an influence on savoring. Adversity intelligence is defined as an individual's ability to face problems and continue to struggle when experiencing difficulties in his life by controlling problems, understanding problems, limiting problems to aspects of life, and considering the problems at hand to be temporary. So that savoring can increase adversity intelligence in addition to increasing happiness in a person. Because with the savoring in a person, the adversity intelligence will increase. The study used a correlational research design with a sample size of 180 students. Data were collected using simple random sampling technique. Instrument using Savoring Beliefs Inventory (SBI) and Adversity Intelligence Scale. The data analysis technique used the Pearson Product Moment (PPM) correlation method to determine the relationship between savoring and adversity intelligence among students. The relationship between savoring and adversity intelligence was found to be positively correlated. All dimensions of savoring and adversity intelligence were found to be positively correlated. Based on the research results, the more students have high savoring, the higher their adversity intelligence.